Security in the Global Commons and Beyond
XXIV, 222 p. 31 illus., 28 illus. in color.
Keywords: This book deals with two areas: Global Commons and Security: inextricably melted together and more relevant than ever in a world which is ever globalized and… with an incognita looming on the horizon: the effects of the Coronavirus pandemic upon the International Relations and globalization. Global Commons have always been relevant. It was Mahan who argued that the first and most obvious light in which the sea presents itself from the political and social point of view, is that of a great highway; or better, perhaps, of a wide common… Nowadays, this view has been further developed and, in addition to the unique legal implications that the Global Commons introduce, they are viewed, more and more intently, as a common pool of resources. Or perhaps, not that common… Resources, the key word! Which has to be always supplemented by two key words: access and security. And still, another one: data, the cyberspace contribution to the equation.